Current Trends in Magnesium (Mg) Research - Sunkari, Sailaja S. (IntechOpen, 2022)
Current Trends in Magnesium (Mg) Research discusses recent research activities in which magnesium plays a central role, in its several forms as composites, alloys, or compounds. Mg alloys/composites/compounds are widely used in the transportation industry (both air and ground) and medical industry (bone/dental implants) and are being tested for use in the energy sector as alternatives to Li-ion batteries. Chapters address such topics as the role of Mg in diverse fields, the environmental impact of Mg processing technologies, Mg as a biomaterial in aiding the growth of bone tissues, corrosion protection of Mg alloys, the wear behavior of Mg hybrid composites, and synthesis of Mg compounds for practical applications in industry.